Pengaruh Penambahan NaCl sebagai Stress Agent dalam Kultivasi Sel Mikroalga Dunaliella tertiolecta ATCC 30929 terhadap Akulumasi Lipid Intrasel - Karseno Karseno; M. Takagi; T. Yoshida (agriTECH, 2004)
Lipid composition of microalgae cell was affected by saline medium. Increasing of initial NaCI in modified NORO medium from 0.5 M to 1.0 M resulted in an increase of intracellular lipid content of Dunaliella tertiolecta ATCC 30929 cell from 60% to 67% (db). Loading of 0.5 M NaCI at a middle of logarithmic phase or 1.0 M at the end of logarithmic phase during the growth on the same medium increased intracellular lipid content to 70% (db). Addition of NaCI up to 2.0 M during the culture gave a high intracellular lipid content up to 77% (db) , although cell concentration was decreased to a half The temperature, light intensity, and aeration was adjusted at 30 Â°C, 150 mo1.11.m-2 (10.000 lux) and 250 ml/min CO2 enriched air (CO2 3%).